Initial public offerings and venture capital in Germany - Stefanie A. Franzke; Stefanie Grohs; Christian Laux (Goethe University Frankfurt, Center for Financial Studies (CFS), 2003)
We present a survey on the role of initial public offerings (IPOs) and venture capital (VC) in Germany after the Second World War. Between 1945 and 1983 IPOs hardly played a role at all and only a minor role thereafter. In addition, companies that chose an IPO were much older and larger than the average companies going public for the first time in the US or the UK. The level of IPO underpricing in Germany, in contrast, has not been fundamentally different from that in other countries. The picture for venture capital financing is not much different from that provided by IPOs in Germany. For a long time venture capital financing was hardly significant, particularly as a source of early stage financing. The unprecedented boom on the Neuer Markt between 1997 and 2000, when many small venture capital financed firms entered the market, provides a striking contrast to the preceding era. However, by US standards, the levels of both IPO and venture capital activities remained rather low even in this boom phase. The extent to which recent developments will have a lasting impact on the financing of German firms, the level of IPO activity, and venture capital financing, remains to be seen. At the time of writing, activity has come to a near stand still and the Neuer Markt has just been dissolved. The low number of IPOs and the fairly low volume of VC financing in Germany before the introduction of the Neuer Markt are a striking and much debated phenomenon. Understanding the reasons for these apparent peculiarities is vital to understanding the German financial system. The potential explanations that have been put forward range from differences in mentality to legal and institutional impediments and the availability of alternative sources of financing. Moreover the recent literature discusses how interest groups may have benefited and influenced the situation. These groups include politicians, unions/ workers, managers/controlling-owners of established firms as well as banks.
urn:nbn:de:hebis:30-10310
Keywords: G10; G24; G14; 330; Initial Public Offering (IPO); Venture Capital; Germany